Biological invasions economic and environmental costs of alien plant, animal, and microbe species - Pimentel, David, 1925- (CRC Press, 2011)
"A revised, expanded, and updated second version to the successful Biological Invasions: Economic and Environmental Costs of Alien Plant, Animal, and Microbe Species, this reference discusses how non-native species invade new ecosystems and the subsequent economic and environmental effects of these species. With nine new chapters, this text provides detailed information on the major components of the invasive-species problem from six continents, including impacts on human health and livestock. The book examines ways in which non-native species destroy vital crops and forests; damage ecosystem dynamics, which leads to plant and animal biodiversity losses; and cause soil erosion and water loss"--